Creep behavior of C/SiC composite in hot oxidizing atmosphere and its mechanism. Issue 12 (15th August 2017) - Su, Fei; Huang, Pengfei; Wu, Jianguo; Chen, Bo; Wang, Qizhi; Yao, Ruixia; Li, Tenghui; Pan, Xiaoxu
Abstract: Creep test of C/SiC composite with and without protective layer under various stresses and temperatures in hot oxidizing atmosphere were conducted. Specimens with oxidation protective layer demonstrated much lower strain rate. Based on the equivalent steady state strain rates from these tests, phenomenological creep models were developed. Moreover, the micro-mechanism of creep of C/SiC material were investigated. First, oxidation progress of T-300 carbon fiber and C/SiC composite were quantitatively evaluated with the aid of thermo-gravity-analysis (TGA) and high precision balance (100 mg, 0.1 mg) respectively. It was found that oxidation of T300 carbon fiber became evident above 600 °C in hot atmosphere, and for C/SiC composite specimen at 850 °C, the oxidation protective layer could lower the oxidation rate by 80% during the first 10 h of high temperature testing. SEM analyses of the cross section of the C/SiC specimen after 10 h of thermal loading in hot oxidizing atmosphere showed that oxidation of C/SiC composite started from the periphery and extended into the interior by ablating the carbon fibers. Fibers of specimen without the oxidation protective layer were ablated totally. A creep test of the C/SiC composite with all fiber ablated (i.e. only SiC matrix remaining)was performed showing that the creep rate of the matrix to be nearly zero. By correlating all these experimental findings, we conclude that the creep mechanism of C/SiC composite in hot oxidizing atmosphere is due to and controlled by the oxidation/ ablation of carbon fibers.